Environmental Factors Associated With Type 1 Diabetes Mellitus - Raad Ghareeb , Safa; Ibrahim Alezzi, Jalil; Jasim Mohammed, Aseel (Diyala Journal of Medicine, 2021)
Background: Type 1diabetes (T1D) is immune-mediated disease that presented as a consequence of the gradual destruction of the insulin- producing beta cells, which in results total beta-cell loss and complete dependence on exogenous insulin. Objective: To explore the potential environmental risk factors associated with the development of T1D among children. Patients and Methods: This case-control study was conducted in the pediatric department of Albatool teaching hospital in Diyala province, Iraq. A hundred children diagnosed with diabetes mellitus type1 (cases) and hundred children (controls) without diabetes during the period between February 2020 to May 2020. Data collection was done through interviewing parents’ or the caregivers of children directly using a questionnaire that was used before for study T1D. the target population was the children attending the outpatient clinic of the endocrine pediatric department of Albatool teaching hospital. A total of 200 children were included in the study. Computer software SPSS (Version 25) and Microsoft Excel (2016) were used to carry out the statistical analysis of data. Results: The results show Children who had insufficient family income had the highest risk for developing T1D (p<0.001), and children born to low educated parents, especially illiterate parents, had a risk to develop T1D (p< 0.001), followed by children whose parent had a history of consanguinity had a high risk for developing T1D (p=0.004). Children born to older mothers had a higher risk for developing T1D (p=0.04). Children with cesarean section delivery had more risk to develop T1D (p <0.000), followed by children a history of early onset of weaning had more risk to develop T1D (p= 0.001). Children had a history of bottle feeding had more risk to develop T1D (p= 0.004). Conclusion: The following factors were associated with significant risk for developing type 1 DM in children: Insufficient family income, low educated parents especially illiterate parents, history of consanguinity. Maternal factors, including older mothers, mothers with a previous history of abortion and infection, and a history of abnormal weight gain. Child factors include, including a history of hospital delivery, a low birth weight, an early onset of weaning, and bottle-feeding.